2015
DOI: 10.1039/c4gc01328j
|View full text |Cite
|
Sign up to set email alerts
|

Metal-free hydroacyloxylation and hydration reactions of ynamides: synthesis of α-acyloxyenamides and N-acylsulfonamides

Abstract: Two types of highly efficient and operationally simple reactions of ynamides under metal-free conditions are developed, including hydroacyloxylation and hydration, which afforded highly functionalized α-acyloxyenamides and pharmaceutically important N-acylsulfonamides in good to excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(42 citation statements)
references
References 27 publications
1
40
0
1
Order By: Relevance
“…Ynamides are sufficiently reactive to allow the addition of simple carboxylic acids. [8] Similarly,benzoic acid or acetic acid could be added to 3,3-diisopropyl-1-(phenylethynyl)triazene (toluene,1 00 8 8C, 24 h) to give products 4 (91 %y ield) and 5 (94 %y ield). Again, the E isomer was obtained as the major product isomer (Scheme 2).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ynamides are sufficiently reactive to allow the addition of simple carboxylic acids. [8] Similarly,benzoic acid or acetic acid could be added to 3,3-diisopropyl-1-(phenylethynyl)triazene (toluene,1 00 8 8C, 24 h) to give products 4 (91 %y ield) and 5 (94 %y ield). Again, the E isomer was obtained as the major product isomer (Scheme 2).…”
mentioning
confidence: 99%
“…To conclude,w eh ave started to examine the chemical reactivity of 1-alkynyltriazenes,which can be prepared easily by ar ecently developed method. [4] On purpose,w eh ave not performed ad etailed study on scope and limitations for one or two selected reactions.I nstead, we have examined different types of reactions in order to obtain af irst impression of the general reactivity.T he results show that 1-alkynyltriazenes are activated alkynes,w hich undergo av ariety of chemical transformations.T he reactivity observed so far is reminiscent of what has been reported for ynamides.T he extent of the similarity between 1-alkynyltriazene and ynamide reactivities needs to be examined in future studies, but it seems likely that the transformations reported herein are merely the tip of the iceberg with respect to possible reactions of 1-alkynyltriazenes.O ne interesting aspect of these reactions is the possibility to access triazenes,w hich would be otherwise difficult to synthesize.F or example,i ti s unlikely that the olefinic triazenes described above (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)can be prepared by the standard synthetic route for triazenes.I n view of the fact that aromatic triazenes have been investigated extensively as potential antitumor agents,i tw ill be interesting to perform biological tests with these new olefinic triazenes.Asecond noteworthy point is the intrinsic reactivity of triazene-containing compounds.D espite the fact that the relative stability of the compounds means that handling and purification (for example,b yc hromatography) are quite straightforward, it is possible to substitute the triazene functionality with other groups,a sd emonstrated by the formation of compounds 23-27.T aken together,o ur results suggest that 1-alkynyltriazenes should become valuable reagents for synthetic organic chemistry.…”
mentioning
confidence: 99%
“…Die trifluormethylierten tertiären chiralen Alkoholgruppen stellen ein zunehmend attraktives Motiv mit potenziellen medizinischen Anwendungen dar, [20] [23] Eine metallfreies Verfahren, das moderate bis hohe Ausbeuten allerdings bei noch hçheren Temperaturen (100 8 8C) ermçglicht, wurde vor kurzem publiziert. [24] Wirs tellten fest, dass die Hydroacyloxylierung von 3 mit Essig-und Benzoesäure in Dichlormethan bei Raumtemperatur ohne Verlust der Enantiomerenreinheit gelingt. In beiden Fällen wurden die E-Isomere mit hoher Diastereoselektivität (E/Z > 99:1) produziert und wir erhielten 29 und 30 in 89 %b zw.9 3% Ausbeute [Gleichungen (4) und (5) in Schema 2].…”
Section: Angewandte Chemieunclassified
“…in toluene at 100 °C (52-99% isolated yields after 1 h). 97 Further studies carried out by other research groups revealed the possibility of carrying out these addition processes under milder conditions, i.e. in CH2Cl2 at r.t., although the reaction times required in these cases were much longer (12-65 h).…”
Section: Metal-free Reactionsmentioning
confidence: 99%